2005
DOI: 10.1017/s0954579405050224
|View full text |Cite
|
Sign up to set email alerts
|

Do parents respond in different ways when children feel different emotions? The emotional context of parenting

Abstract: When children experience emotions, do they view their primary caregiver as reacting in a different manner depending on the children's different emotions? Parental socialization of negative emotions and child psychopathology were examined among 161 inner city youth ages 11-14 years. These early adolescents were more likely to perceive their parents as responding in a different manner to different emotions than responding in the same way to different emotions. In addition, we asked if emotion-specific socializat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
235
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(262 citation statements)
references
References 47 publications
(48 reference statements)
12
235
4
3
Order By: Relevance
“…In another study, children's emotional difficulties were found to be related to parents' lack of accepting or supportive responses (O'Neal, & Magai, 2005). Yagmurlu and Altan (2010) indicated that inhibited young Turkish children had a low level of emotion regulation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, children's emotional difficulties were found to be related to parents' lack of accepting or supportive responses (O'Neal, & Magai, 2005). Yagmurlu and Altan (2010) indicated that inhibited young Turkish children had a low level of emotion regulation.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have indicated that parents', especially mothers', reactions to their children's emotions are strongly related to children's emotional competence (Denham & Kochanoff, 2002;Denham, Bassett, & Wyatt, 2007;Hastings & De, 2008;Fabes, Leonard, Kupanoff, & Martin, 2001;O'Neal & Magai, 2005;Ramsden & Hubbard, 2002;Yagmurlu & Altan, 2010). If parents react negatively towards their children's emotional displays, children feel anxious whenever they again face an emotionally evocative situation.…”
Section: Introductionmentioning
confidence: 99%
“…proposed the Emotions as a Child Scales Inventory (EAC) that includes the Emotion Socialization Scale (ESS). The ESS assesses youth's perception about how parents react to their NE and features five parental emotion socialization strategies (Klimes-Dougan et al, 2007;O'Neal & Magai, 2005). The positive strategy, reward, comprises parental behaviors that foster the reduction of negative affect, while promoting the adolescent's tolerance to all NE by providing comfort, empathizing, and problem solving (Malatesta-Magai, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, Tomkins and Magai's predictions have been supported (Kehoe et al 2014;Klimes-Dougan et al 2007;O'Neal & Magai, 2005), with contradictory findings regarding override, as it is not always associated with negative outcomes (Klimes-Dougan et al 2007. Override also includes distracting parental behaviors that in conjunction with an emotionally acceptant stance may be supportive of youths' regulatory efforts (Klimes-Dougan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, mothers who were more likely to engage in unsupportive and harsh emotion socialization behaviors (i.e., were negative, more rejecting of emotions, and who less often discussed emotional experiences) had children who were less able to self--report on their sadness, who spent more time engaging in talk that was unrelated to the emotional expression, who were reported to be more negative and labile, and had lower emotion regulation abilities (Davidov & Grusec, 2006;Shaffer et al, 2012;Warren & Stifter, 2008). A retrospective, self--report study of parental responsiveness during childhood found associations between perceived parental responses to emotions and maladaptive outcome (O'Neal & Magai, 2005). More specifically, children who reported more symptoms of behavioral difficulties at ages 11 to 14 years perceived their parents as more frequently rewarding their feelings of shame (e.g., offering comfort following their child's expression of shame) and magnifying their feelings of anger (e.g., responding with anger to their child's expressed anger) when they were younger.…”
Section: Parental Responses To Emotional Expressions Of the Childmentioning
confidence: 99%